Translation from the data of clinical trials to precision medicine: limitation of the current risk score for predicting coronary thrombosis and major bleeding - Ahn, Jong-Hwa; Jang, Jeong Yoon; Jeong, Young-Hoon (Journal of Thoracic Disease; Vol 8, No 9 (September 28, 2016): Journal of Thoracic Disease, 2016)
In his 2015 State of the Union address, President Obama announced that he’s launching the Precision Medicine Initiative—a bold new research effort to revolutionize how we improve health and treat disease (1). Until now, most medical treatments have been designed with a “one-size-fits-all” approach, which can be very successful for some patients but not for others. On the other hand, “precision medicine” is an innovative approach that calls for individual differences depending on people’s genes, biomarkers, environments, and lifestyles.